Negara dan Kapasitas Adopsi Inovasi: Studi Kasus Tranformasi Pertahanan Indonesia Periode 1998-2014 - Dzikri, Ilman (Global: Jurnal Politik Internasional, 2016)
This article attempts to explore the explanative factor behind the ineffective Indonesian security sector reform. In general, Indonesian military reform can be divided into several aspects: normative regulative framework), substantive (military doctrine), structural (military organization) and defense economics. This article applies Horowitz’s framework of military diffusion, which mainly sees financial intensity and organizational capital as the principal factors in explaining military innovation adaptability in international systems. At the end of this article, I conclude that both aspects have proven to be the main factors behind Indonesian ineffective defense transformation.